International Interdependencies Of Stock Markets: How Influential Are Well-Established Exchanges In Affecting Movements On The Klse? - Abdullah, Mat Saad; Abdullah, Ismail (Asian Academy of Management (AAM), 2001)
Several analysts assert that linkages among economies primarily, determine the tendency for stock markets to move together across countries. National stock markets from the countries, which have close trade relations, are believed to be highly correlated. If this is the reality, given the openness of the Malaysian economy, how influential are foreign (well-established ) equity markets in affecting movements on the Kuala Lumpur Stock Exchange (KLSE)?